Automated inferior tear meniscus height measurement in a sequence of video - Che Azemin, Mohd Zulfaezal; Ithnin, Mohd. Hafidz; Mohd Kamal, Khairidzan (2012)
Video analysis of the dynamics of the tear meniscus height (TMH) have been used in the diagnosis of dry eye. However, the existing techniques require substantial manual intervention. This research work aims to automate the process of estimating the change in the inferior TMH without manual intervention.